DEVELOPMENT OF GUIDED INQUIRY-BASED E-MODULE ON COLLIGATIVE PROPERTIES OF SOLUTIONS TO IMPROVE SCIENCE LITERACY ABILITY AND CHEMISTRY LEARNING OUTCOMES - Winarni, Endang; Samosir, Hotlan; Samosir, Rendra Christian (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
Abstract: This study aims to the feasibility of guided inquiry-based Chemistry e-modules on the material of colligative properties of solutions, improve science literacy skills and learning outcomes of students. The research sample was the population of class XII MIPA3 SMA Negeri 1 Bintuni with a total of 33 students. Data collection using purposive sampling technique, Research instruments are material feasibility validation sheet and media feasibility, teacher response sheet, student response sheet, The results showed: 1) The feasibility of chemistry e-modules from material expert validators and media experts is 97% very feasible category, 88% teacher response is very good category, and 91% student response is very good category. 2) Students' science literacy skills average n-Gain test 0.46 medium category. 3) Increased learning outcomes of students on average n-Gain test 0.56 medium category. Keywords: Quided Inquisiry; Chemistry E-Module; Colligative Properties Of Solutions Abstrak: Penelitian ini bertujuan untuk kelayakan e-modul Kimia berbasis guided inquiry pada materi sifat koligatif larutan, meningkatkan kemampuan literasi sains dan hasil belajar peserta didik. Sampel penelitian adalah populasi kelas XII MIPA3 SMA Negeri 1 Bintuni dengan jumlah 33 peserta didik. Pengumpulan data menggunakan teknik purposive sampling, Instrumen penelitian yaitu lembar validasi kelayakan materi dan kelayakan media, lembar respon guru , lembar respon peserta didik, Hasil penelitian menunjukkan: 1) Kelayakan e-modul kimia dari validator ahli materi dan ahli media sebasar 97% kategori sangat layak, respon guru 88 % kategori sangat baik, dan respon peserta didik 91% kategori sangat baik. 2) Kemampuan literasi sains peserta didik rata-rata uji n-Gain 0,46 kategori sedang. 3) Peningkatan hasil belajar peserta didik ratarata uji n-Gain 0,56 kategori sedang. Kata Kunci: Quided Inkuiry; E-Modul Kimia; Sifat Koligatif Larutan